2013
DOI: 10.1161/circep.111.000028
|View full text |Cite
|
Sign up to set email alerts
|

Transseptal Conduction as an Important Determinant for Cardiac Resynchronization Therapy, as Revealed by Extensive Electrical Mapping in the Dyssynchronous Canine Heart

Abstract: Background-Simple conceptual ideas about cardiac resynchronization therapy assume that biventricular (BiV) pacing results in collision of right and left ventricular (LV) pacing-derived wavefronts. However, this concept is contradicted by the minor reduction in QRS duration usually observed. We investigated the electric mechanisms of cardiac resynchronization therapy by performing detailed electric mapping during extensive pacing protocols in dyssynchronous canine hearts. Methods and Results-Studies were perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
45
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 33 publications
(37 reference statements)
10
45
0
Order By: Relevance
“…The induced dyssynchrony seen here was similar to a previous porcine and canine models [7,8], and recapitulates abnormalities found in patients with electrical cardiac dyssynchrony. That is, the QRSi produced an average increase of 81% from the mean baseline QRS width in complete LBBB, and 39% for incomplete.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The induced dyssynchrony seen here was similar to a previous porcine and canine models [7,8], and recapitulates abnormalities found in patients with electrical cardiac dyssynchrony. That is, the QRSi produced an average increase of 81% from the mean baseline QRS width in complete LBBB, and 39% for incomplete.…”
Section: Discussionsupporting
confidence: 88%
“…Activation times (ATs) were derived from the recorded and ECGi reconstructed potentials as the time of maximum negative derivative. A number of markers have been developed in conjunction with ECGi to describe quantitatively the electrical dyssynchrony within the heart [6,7]. In this study, the following have been used: Ventricular electrical uncoupling (VEU): the difference in mean activation of the LV and RV free wall.…”
Section: Ecgi Evaluationmentioning
confidence: 99%
“…In terms of mechanical synchrony our results demonstrate that LV-only pacing has favorable outcome which is almost similar to the effect of BIV pacing. While many studies support the notion that LV-only pacing may have beneficial effects in HF patients [26], recent data in children with normal cardiac function and complete AV block demonstrated striking similarity to the results of our rat model in regard to LVonly pacing [27]. Moreover, LV-only pacing appears to be associated with good clinical outcome in this and other studies in the pediatric population [28,29].…”
Section: Discussionsupporting
confidence: 84%
“…Our findings of slow trans-septal conduction are strikingly similar to those recently found in canines. 4 Strik et al 4 found a TSAT of 67±9 ms in a canine model of LBBB and pacing induced dyssynchrony compared with 60±21 ms in our patients with LBBB and heart failure. In the same study, there was no incremental benefit in BIV compared with LV-only pacing, and this was due to predominant LV stimulation in both modes due to long TSATs.…”
Section: Comparison With Previous Studiesmentioning
confidence: 55%
“…We measured only LV endocardial activation time (and not epicardial) and the reduction may be related to changes occurring in the epicardium as has been shown in the canine model. 4 We saw divergent findings for LV epi and BIV epi pacing with an improvement in AHR with BIV epi pacing over LV epi accompanied by a reduction in both QRSd and endocardial LVTAT. The electric findings may be accounted for by the fact that pacing from the epicardium Figure 1.…”
Section: Endocardial Pacing Hemodynamics and Electric Changesmentioning
confidence: 88%